The mechanism of influence of polyvinyl alcohol (9 kDa) on the formation of ice crystals in aqueous solutions - Dyubko, T. S.; Pivovarenko, V. G.; Kuleshova, L. G.; Chekanova, V. V.; Hvozdiuk, Ya. V.; Pakhomova, Yu. S.; Kompaniets, A. M.; Falko, Ο. V.; Tatarets, A. L. (Low Temperature Physics 48, 734 (2022), 2022)
Preventing crystallization of the liquid phase during freeze-thawing of cells is one of the main problems that need to be solved for the successful preservation of biomaterial at low temperatures. One highly effective recrystallization inhibitor is polyvinyl alcohol (PVA). However, the mechanisms of its cryoprotective effect have not been finally elucidated. In particular, it is not clear which structural features contribute to the realization of the antirecrystallization properties of PVA in the region of its cryoprotective concentrations. The influence of PVA on solvent crystallization and structural rearrangements of associations of PVA molecules in phosphate-buffered saline (PBS) was experimentally investigated. Solutions of PVA (molecular weight 9 kDa) in PBS were studied by cryomicroscopy and fluorescence spectroscopy methods. It was shown that molecular associations of PVA in PBS undergo a rearrangement of about 0.5−1 wt%, which is accompanied by a change in their size and hydrophilic-hydrophobic properties. PVA also changes the morphological structure of ice upon cooling and prevents crystallization upon heating. It is suggested that the mechanism of the antirecrystallization activity of PVA may be due to the formation of its complexes with the surface of ice crystals.
Keywords: polyvinyl alcohol, crystallization, structural rearrangements, fluorescence.